Letramento visual: uma percepção da aprendizagem de alunos surdos no ensino médio - Viana Neto, Francisco de Acací (Universidade Federal Rural do Semi-Árido, 2019)
The research carried out at the regular school, located in the interior of the Potiguar backwoods, is focused on the perception and understanding of the visual experience for the deaf and its relation with visual literacy. Considering that it presents a methodology of teaching with multimodal elements for the learning of Libras in regular school,especially the High School, evidencing the visual elements for the deaf in the strategy of language teaching in the school context and on the perception of the deaf students who are involved in this process, enabling this research study with the interpreters translators and their experiences. His general objective is to analyze the learning of Libras of deaf high school students in a public school in the city of Caraúbas by the visual literacy. To help the general objective, I propose through the specific objectives: To perceive how the visual literacy of deaf students in the learning of Libras; to find out what strategies are used in teaching for deaf students; to analyze the possibility of educational action of the students in order to learn with their visual perception about the methodologies of the teaching of Libras. Methodologically, the study developed is a qualitative research, of descriptive and exploratory character, used to collect data from the semi-structured interview as the questionnaire containing, for deaf students, the open questions with images, besides the researcher's requests in Libras, being exposed to visual resources, for translators interpret, with open questions, that made it possible to register the opinion of the participants, where it was made and about their experiences, as well as possible facilities or difficulties in the use of certain products and systems of communication. Then, with the analysis of the discussions, one can see what is happening in the school context of literacy to which the deaf students learn, naturally, within visual communication, among so many other possibilities of connection.
Monografia
Keywords: Letramento visual; Multimodalidade; Alunos surdos; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS LIBRAS